2024
DOI: 10.3390/ijms25042159
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte Antioxidant Enzymes mRNA Levels versus Reticulocyte Maturity Indices in Hereditary Spherocytosis, β-Thalassemia and Sickle Cell Disease

Daniela Melo,
Fátima Ferreira,
Maria José Teles
et al.

Abstract: The antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and peroxiredoxin 2 (Prx2) are particularly important in erythroid cells. Reticulocytes and other erythroid precursors may adapt their biosynthetic mechanisms to cell defects or to changes in the bone marrow environment. Our aim was to perform a comparative study of the mRNA levels of CAT, GPX1, PRDX2 and SOD1 in reticulocytes from healthy individuals and from patients with hereditary spherocytosis (HS), sickle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Due to different genetic mutations, changes in the erythroid cell antioxidant capacity may start early on, along with erythropoiesis [ 87 ]. Very recently, by studying circulating reticulocytes from patients with these types of NHIA, we found that only in the reticulocytes from unspl HS were the mRNA levels of Prx2 positively correlated with reticulocyte maturity indices [ 88 ]. In fact, the importance of Prx2 in the development of erythroid precursor cells has been reported in other studies [ 4 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to different genetic mutations, changes in the erythroid cell antioxidant capacity may start early on, along with erythropoiesis [ 87 ]. Very recently, by studying circulating reticulocytes from patients with these types of NHIA, we found that only in the reticulocytes from unspl HS were the mRNA levels of Prx2 positively correlated with reticulocyte maturity indices [ 88 ]. In fact, the importance of Prx2 in the development of erythroid precursor cells has been reported in other studies [ 4 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…In RBCs from SCD patients, the changes in membrane structure, cytoskeleton, and lipid organization due to HbS sickling may alter the interactions between the RBC membrane and antioxidant enzymes, explaining the different membrane antioxidant profile, with a reduced amount of each enzyme bound to the membrane ( Figure 1 ). Interestingly, we showed that SCD individuals presented an immature reticulocyte population with high mRNA levels of CAT , GPX1 , and PRDX2 [ 88 ]. These data suggest that, although reticulocytes from SCD patients present with the potential for increased amounts of CAT, GPx, and Prx2 in mature erythrocytes, this is not reflected in the binding of these enzymes to the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SLC22A4 mRNA is detectable in human hematopoietic stem cells [ 41 ] and may be relevant in the context of polycythemia vera [ 108 ]. In addition, given that different types of reticulocytes are identifiable, and that they may vary in their antioxidant “machinery” [ 5 ], it would be interesting to evaluate SLC22A4 mRNA and ESH levels in these cell types, particularly in disease settings that induce stress erythropoiesis. Finally, given the increasing sensitivity in identifying additional components of the human and murine RBC proteome [ 109 ], it would be important to determine definitively, using highly purified samples of mature RBCs, lacking leukocytes and platelets, whether or not the SLC22A4 transporter protein is present and functional on these cells.…”
Section: Esh and Rbc Biologymentioning
confidence: 99%
“…These include small molecules (e.g., vitamin C, vitamin E, reduced glutathione (i.e., GSH)) and proteins (e.g., superoxide dismutase, glutathione peroxidase, catalase, peroxiredoxin 2), which can eliminate ROS by participating in specific metabolic pathways. In addition, multiple redundant pathways repair RBC lipids and proteins damaged by oxidant stress (for reviews, see [ 3 , 4 , 5 ]), and enzymes that maintain antioxidant capacity continually replenish these pathways (e.g., glutathione reductase). To this end, the relevant small molecules, proteins, enzymes, reactions, and metabolic pathways have been studied intensively for decades in an effort, not only to understand how RBCs experience and respond to oxidant stress in health and disease, but also to develop approaches to enable RBCs to avoid and resist oxidant stress and enhance their abilities to ameliorate it [ 6 ].…”
Section: Introductionmentioning
confidence: 99%